A Compact Review of IPMC as Soft Actuator and Sensor: Current Trends, Challenges, and Potential Solutions From Our Recent Work - Hao, Muyu; Wang, Yanjie; Zhu, Zicai; He, Qingsong; Zhu, Denglin; Luo, Minzhou (Frontiers in Robotics and AI, 2019)
Recently, attempts have been made to develop ionic polymer–metal composite (IPMC), which is garnering growing interest for ionic artificial muscle, as a soft actuator and sensor due to its inherent properties of low weight, flexibility, softness, and particularly, its efficient transformation of electrical energy into mechanical energy, with large bending strain response under a low activation voltage. In this paper, we focused on several current deficiencies of IPMC that restrict its application, such as non-standardized preparation steps, relaxation under DC voltage, solvent evaporation, and poor output force. Corresponding solutions to overcome the abovementioned problems have recently been proposed from our point of view and developed through our research. After a brief introduction to the working mechanism of IPMC, we here investigate the key factors that influence the actuating performance of IPMC. We also review the optimization strategies in IPMC actuation, including those for preparation steps, additive selection for a thick casting membrane, solvent substitutes, water content, encapsulation, etc. With consideration of the role of the interface electrode, its effects on the performance of IPMC are revealed based on our previous work. Finally, we also discuss IPMCs as potential sensors theoretically and experimentally. The elimination of the deficiencies of IPMC will promote its applications in soft robotics.